Pick-and-verify: verification-based highly reliable picking system for various target objects in clutter. (19th March 2017) - Wada, Kentaro; Sugiura, Makoto; Yanokura, Iori; Inagaki, Yuto; Okada, Kei; Inaba, Masayuki
Abstract: The reliability of picking task for various objects in clutter, as measured on the Amazon Picking Challenge, is far from the expectations of automation companies. Even if the best-performed team, who run object detection before picking the object, had picked a wrong object in the competition. In this paper, we propose a practical method to compose a highly reliable picking system with verification-based approach to reduce the rate of wrong picking and raise the reliability of picking ordered objects. In our approach, which we call pick-and-verify, the robot recognizes object twice: in clutter scene to detect the target and in hand after picking an object with less time loss and rise of reliability of picking the target. For grasping the detected object we do not assume its pose and it is actually the target object, instead, we adopt vision-based grasp planning for vacuum gripper with sensed 3-D point cloud. With the presented approach, the reliability of picking target objects raised 50%, and the score in the APC2015 competition has been improved to be close to the best-performed team by picking 9 out of 12 objects in 10 min with the same hardware in our previous system. Graphical Abstract: